Preposition pairs - Ivana Matas Ivanković; Barbara Kovačević (Rasprave Instituta za Hrvatski Jezik i Jezikoslovlje, 2007)
In this paper the authors consider prepositions that often appear in pairs (e.g. od and do, iz and u, s and na), showing semantic and structural pair integrity (showing, namely, that such prepositions only become meaningful in pairs). This integrity can also be seen in their frequent idiomatic use. The paper provides a thorough outline of preposition pair analysis in dictionaries and of their status in literature. It is demonstrated that preposition pair analysis in Croatian monolingual dictionaries is inconsistent, i.e. nonsystematized. The following analyzes semantic features of such prepositions and classifies them into several groups according to their meaning. Furthermore, the paper considers syntactic features of such prepositions (they are used as adverbials, attributes or parts of nominal predicates). When it comes to identification of syntactic (sentence) idiom function, the authors point out that some structural types are predetermined for particular syntactic functions, e.g. all structurally verbal idioms with preposition pairs in this paper are of the verbal categorical meaning, and they will all have a predicative function in the sentence. In conclusion, the paper proposes a preposition pair methodology for monolingual dictionaries of the contemporary Croatian language, and provides a model of preposition pair idiom analysis.